Optimization of fermentation conditions for the production of bioactive phenolic compounds from palm oil mill effluent using Aspergillus niger IBS-103ZA - Zulkarnain Mohamed Idris (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The present investigation is an effort to develop an environmentally friendly and cost effective liquid-state fermentation process by introducing a new locally isolated fungal strain of Aspergillus niger for the production of phenolics from a new source, palm oil mill effluent (POME). Screening result for the search of potential fungal strain showed that IBS-103ZA strain gave the highest amount of phenolics (639.90±4.19 GAE mg/l). A sequential optimization based on statistical design and one-factor-at-atime (OFAT) method was employed to optimize the fermentation conditions for the improvement in phenolics production. The results obtained from Plackett-Burman analysis found that out of eleven variables studied, sucrose, manganese sulfate (MnSO4) and incubation temperature were the major factors for further optimization. Based on OFAT method, the selected media components (sucrose and MnSO4) and process parameter (incubation temperature) were optimized by the face centered central composite design (FCCCD) under response surface methodology (RSM). The statistical analysis showed that the optimum fermentation conditions were found at 5.39% (w/v) sucrose, 2.22% (w/v) MnSO4 and a temperature of 35° C with other fixed parameters. The phenolics production increased significantly to 949.56±3.82 GAE mg/l. The antioxidant activity of the fermented POME extract (FE) was evaluated through several in-vitro assays: 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, inhibition of β-carotene bleaching, ferric reducing power (FRAP) and inhibition of oxidative hemolysis in human erythrocytes. The results were compared with the synthetic compound, BHT and the unfermented POME extract (UFE). It was found that the FE showed the highest antioxidant activity, based on DPPH scavenging assay (IC50, 0.45±0.13 mg/ml), FRAP assay (FRAP value, 1088.27±34.25 μmol FeSO4.7H2O/g dry sample) and inhibition of oxidative hemolysis (IC50, 0.097±0.020 mg/ml). In case of inhibition of β-carotene bleaching, the FE showed percentage of inhibition of 79.10±5.55% at 0.1 mg/ml of concentration. The phenolics that were present in extracts were identified and quantified by high performance liquid chromatography (HPLC). Eight out of nine compounds matched with the phenolic acid standards: Gallic, protocatechuic, 4-hydroxybenzoic, 4-hydroxyphenyl acetic, caffeic, syringic, p-coumaric and ferulic acids. It was observed that only 4- hydroxybenzoic and syringic acids decreased while other phenolic acids increased in the content after the fermentation. Among these phenolic acids, the content of gallic acid improved remarkably by 12-fold through the fermentation. The potential use of Aspergillus niger IBS-103ZA to treat the effluent for removal of COD and heavy metals were also evaluated. The percentages of COD and Zn2+ ions removal were 24.44% and 24.79% respectively after 120 hours of fermentation. The Pb2+ ions were totally removed after 72 hours of fermentation. No Cd was detected in POME during the study. Thus, fermentation of POME with Aspergillus niger IBS-103ZA not only increased its value added product but also reduced the pollution load in the effluent.